El rendimiento en la enseñanza a distancia - Sarramona López, Jaime (Teoría de la Educación. Revista Interuniversitaria, 2009)
The performance use to be a critic theme in distance learning, although there is data enough to judge it objectively. There are performances inhérents to the system, as the habit of autotraining or the discipline to study, with the knowledge and the possibility to incorporate habilities. Only the objectives with social aspects may remaine out of the normal achivements. The discance training, with aplication in the labor world developes an institutional culture of autotraining, which facilitates retraining and permanent education. We can not forget the consequences on the autors -trainers and tutors-, especialy in relation to the organizational habits and the strict planification of the educational process.